The Study of Nursing During the Postpartum Period from the Perspective of Aceh Culture in Gampong Asan Kareung, Lhokseumawe City - Cut Linar; Muhammad Badiran; Rina Hanum (Journal La Medihealtico, 2020)
Postpartum care is a treatment for mothers who are about to give birth or have just given birth so that their reproductive organs return to normal. Madeung is a medical technique commonly used by Acehnese women who have just finished giving birt. The purpose of this study was to explore the study of postpartum care (madeueng) from the perspective of Aceh culture in the village of Kareung Asan, the city of Lhoekseumawe. This type of research is descriptive qualitative with the approach used by researchers in this study is the ethnographic approach. The characteristics of the main informants were postpartum mothers who carried out the madeung process, while the triangulation informants were family and health workers (midwives). The results made, but the factors that motivated parents to carry out the madeng process are sometimes still considered negative. Informants are influenced by experienced users of parents, which results in them imitating negative habit patterns and perceiving some processes as commonplace. Parents often provide user experiences to parents, who live in them imitating negative habit patterns and perceiving some processes that are created as mater, of course. Parents often provide experiences about madeung and all informants have an adequate level of process. It is recommended that mothers who have just given birth and are about to undergo the madeung ritual to have their own firmness in determining their choices regarding personal health, especially regarding the anxiety of abstinence and advice that must be taken.